Spiritual Well-Being of Adolescents that are Difficult to Manage at School - Kusmawati, Ati; Hadi, Cholichul; Putra, M.G.Bagus Ani (International Journal of Engineering and Technology, 2018)
This research aims to find out the spiritual well being of adolescents that are difficult to manage at school. The method used is the intrinsic case study which aims to understand an intrinsic characteristic of certain cases. The participants consist of 5 students from one of the junior high schools in Jakarta. The researcher conducted a thorough interview and provided assistance by using religious approaches (by praying dhuha, reciting Al-Qur’an, and sharing which is done every morning before the class starts, in other words at 6.30-7.00). The result of this research is that students that are difficult to manage possess lower level of spiritual well being, due to the family’s lack of attention on both the students and their improvements. Parents, school, and friends influence them in many ways. To them, they should listen to what their friends say and act in the same way as their friends. This research also finds out that the reason for students to not listen to their teachers, obey the school rules, and to not listen to their parents are social medias and gadgets. After the assistance using religious approaches, changes in the behavior of the students that are difficult to manage can be found. Among those changes are their willingness to study, devote (pray and reciting Al-Qur’an), utter less harsh words, not play their gadgets during lessons, and try to become a better person.